Dek219 encodes the DICER-LIKE1 protein that affects chromatin accessibility and kernel development in maize - Si-di XIE; Ran TIAN; Jun-jie ZHANG; Han-mei LIU; Yang-ping LI; Yu-feng HU; Guo-wu YU; Yu-bi HUANG; Ying-hong LIU (Journal of Integrative Agriculture, 2023)
Chromatin accessibility plays a vital role in gene transcriptional regulation. However, the regulatory mechanism of chromatin accessibility, as well as its role in regulating crucial gene expression and kernel development in maize (Zea mays) are poorly understood. In this study, we isolated a maize kernel mutant designated as defective kernel219 (dek219), which displays opaque endosperm and embryo abortion. Dek219 encodes the DICER-LIKE1 (DCL1) protein, an essential enzyme in miRNA biogenesis. Loss of function of Dek219 results in significant reductions in the expression levels of most miRNAs and histone genes. Further research showed that the Heat shock transcription factor17 (Hsf17)-Zm00001d016571 module may be one of the factors affecting the expression of histone genes. Assay results for transposase-accessible chromatin sequencing (ATAC-seq) indicated that the chromatin accessibility of dek219 is altered compared with that of wild type (WT), which may regulate the expression of crucial genes in kernel development. By analyzing differentially expressed genes (DEGs) and differentially accessible chromatin regions (ACRs) between WT and dek219, we identified 119 candidate genes that are regulated by chromatin accessibility, including some reported to be crucial genes for kernel development. Taken together, these results suggest that Dek219 affects chromatin accessibility and the expression of crucial genes that are required for maize kernel development.